Altered expression of CmNRRa changes flowering time of Chrysanthemum morifolium. Issue 3 (28th November 2012) - Zhang, Yuman; Lian, Lijuan; Liu, Qing; Xiao, Na; Fang, Rongxiang; Liu, Qinglin; Chen, Xiaoying
Summary Flowering time is an important ornamental trait for chrysanthemum (Chrysanthemum morifolium, Dendranthema x grandiflorum) floricultural production. In this study, CmNRRa, an orthologous gene of OsNRRa that regulates root growth in response to nutrient stress in rice, was identified from Chrysanthemum and its role in flowering time was studied. The entire CmNRRa cDNA sequence was determined using a combinatorial PCR approach along with 5′ and 3′ RACE methods. CmNRRa expression levels in various tissues were monitored by real‐time RT‐PCR. CmNRRa was strongly expressed in flower buds and peduncles, suggesting that CmNRRa plays a regulatory role in floral development. To investigate the biological function of CmNRRa in chrysanthemums, overexpression and knockdown of CmNRRa were carried out using transgenic Chrysanthemum plants generated through Agrobacterium‐mediated transformation. CmNRRa expression levels in the transgenic plants were assayed by real‐time RT‐PCR and Northern blot analysis. The transgenic plants showed altered flowering times compared with nontransgenic plants. CmNRRa‐RNAi transgenic plants flowered 40–64 days earlier, while CmNRRa‐overexpressing plants exhibited a delayed flowering phenotype. These results revealed a negative effect of CmNRRa on flowering time modulation. Alteration of CmNRRa expression levels might be an effective means of controlling flowering time in Chrysanthemum. These results possess potential application in molecular breeding of chrysanthemums that production year‐round, and may improve commercial chrysanthemum production in the flower industry.